2001
DOI: 10.1084/jem.194.12.1777
|View full text |Cite
|
Sign up to set email alerts
|

The Intersectin 2 Adaptor Links Wiskott Aldrich Syndrome Protein (WASp)-mediated Actin Polymerization to T Cell Antigen Receptor Endocytosis

Abstract: Induction of T cell antigen receptor (TCR) endocytosis has a significant impact on TCR signaling and T cell behavior, but the molecular interactions coordinating internalization of the activated TCR are poorly understood. Previously we have shown that TCR endocytosis is regulated by the Wiskott Aldrich Syndrome protein (WASp), a cytosolic effector which, upon interaction with the cdc42 Rho GTPase, couples TCR engagement to Arp 2/3 complex-mediated actin polymerization. Here we report that WASp associates in T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 63 publications
3
126
0
1
Order By: Relevance
“…Intersectin 2L participates with WASP and Cdc42 in the stimulated endocytosis of T-cell antigen receptor (TCR), which is actin dependent. The presence of the DH domain mitigated the inhibitory effects of the rest of intersectin 2L on stimulated TCR endocytosis (McGavin et al, 2001). These studies of intersectin 2L therefore support the suggestion that intersectin 1L acts to link endocytosis and actin cytoskeleton regulation.…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…Intersectin 2L participates with WASP and Cdc42 in the stimulated endocytosis of T-cell antigen receptor (TCR), which is actin dependent. The presence of the DH domain mitigated the inhibitory effects of the rest of intersectin 2L on stimulated TCR endocytosis (McGavin et al, 2001). These studies of intersectin 2L therefore support the suggestion that intersectin 1L acts to link endocytosis and actin cytoskeleton regulation.…”
Section: Introductionsupporting
confidence: 69%
“…Intersectin 1L, localized to peri-active zones Roos and Kelly, 1999), is thus well positioned to switch on actin polymerization in endocytic regions only after a burst of exocytosis. Intersectins promote actin polymerization (Hussain et al, 2001;McGavin et al, 2001) but are inhibitors of endocytosis (Sengar et al, 1999;Simpson et al, 1999;Pucharcos et al, 2000), perhaps because they sequester proteins such as dynamin that are needed for endocytosis. Because dynamin and N-WASP compete with each other for binding to the same SH3 domains of intersectin 1L, inhibition of endocytosis through sequestration of dynamin would be associated with inhibition of N-WASP binding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to endocytosis and exocytosis, intersectin 1 is also involved in actin polymerization [9,20] . Hussain et al reported that the expression of intersectin 1 DH-domain-containing constructs caused the rearrangement of actin specific for Cdc42 activation in cultured cells.…”
Section: Actin Remodelingmentioning
confidence: 99%